Neologisms and their Adaptation to the Galician Language: Case Study Analysis - Freire Armada, Vanesa (Madrygal. Revista de Estudios Gallegos, 2023)
The aim of this research is to analyze and assess the suitability of four different neologisms –tablet, croissant, tweet amd covid-19– which are in process of adaptation or which have already been adapted to the galician language. There are other goals such as demonstrating if the hypothesis: in order for a neologism variant to be utilized by language users, it is necessary for it to be supported by a linguistic authority. The method used here consists of providing a context for the term being analyzed, searching documentation in databases and in a variety of corpora, presenting the results obtained graphically by means of tables, checking the normative nature of the proposals and assessing their suitability for both, its real use and the Galician spelling and phonetics. The main conclusion is that the linguistic norms shall be dynamic regarding the language users needs.